Expression of Public Opinion and Sentiment of Online Gender Antagonism in China-- A Case Study of Yang Li and her Talk Show - Li, Yazheng; Li, Yinghui; Zhong, Huiqi; Liang, Ruihong (Advances in Social Sciences Research Journal, 2022)
In 2020, a Chinese stand-up comedy competition series ‘Rock & Roast’ went viral because of gender issues. Yang Li, one of the comedians, labeled men as "ordinary but confident men" by saying, "How can he be so average, yet so full of confidence?" in the show. In a December episode, she talked about telling a male comedian her new jokes. He replied that she was "testing men's limits." "Do men even have limits?" Yang sarcastically asked, triggering a fresh wave of criticism. Yang Li divides some common issues between men and women into gender, and his own bias will naturally lead to debate. It seems men and women almost "fight" with each other on the Internet. Because of this, this paper took Yang Li and her show as a typical case, mining the review data on Sina Weibo employing various methodological approaches, concluding the content analysis, word frequency analysis, semantic network, and sentimental analysis. In this paper, we objectively showed a trend of user attitude, distinguished different gender groups are negative emotions, presented the evolution of public opinion of each period, and further discussed the reasons for the formation of the "gender antithesis" event and the underlying social problems.